2014
DOI: 10.4103/0019-509x.154046
|View full text |Cite
|
Sign up to set email alerts
|

S100 protein in breast tumor

Abstract: S100 protein is the largest subtribe in calcium binding protein family. According to recent researches, abnormal expression of S100 protein is often related to tumor, including breast tumor. Breast tumor is the most common malignant disease in female with high mortality mainly due to metastasis. Estimating early diagnostic and prognostic markers are helpful to conduct treatment for patients with breast cancer. Accumulating investigations focused on the role of S100 proteins in breast tumor development and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Breast cancer is the most common cancer type among women [79], and especially metastatic breast cancers are highly lethal [80]. It was shown that several S100 family members, including S100A2, S100A4, S100A6, S100A7, S100A8, S100A9, and S100A11 are up-or downregulated in breast cancer compared with healthy tissue, suggesting that S100 proteins play a crucial role in tumour development and progression [81,82] and as predictive biomarkers [83][84][85][86][87][88].…”
Section: S100 Proteins In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer is the most common cancer type among women [79], and especially metastatic breast cancers are highly lethal [80]. It was shown that several S100 family members, including S100A2, S100A4, S100A6, S100A7, S100A8, S100A9, and S100A11 are up-or downregulated in breast cancer compared with healthy tissue, suggesting that S100 proteins play a crucial role in tumour development and progression [81,82] and as predictive biomarkers [83][84][85][86][87][88].…”
Section: S100 Proteins In Breast Cancermentioning
confidence: 99%
“…The interaction between S100A4 and matrix metalloproteinase 2 (MMP2) induces epithelial-mesenchymal transition (EMT), which is considered to be an initial step during invasion and metastasis [95]. S100A4 can not only be found in cancer cells but is also highly expressed in stromal cells of the tumour microenvironment (TME), such as fibroblasts, T-cells, macrophages, and neutrophils [81,96]. Extracellular S100A4 in the TME induces the release of pro-inflammatory factors (e.g., interleukin 6 (IL-6), interleukin 8 (IL-8), and C-X-C motif chemokine 10 (CXCL10)), which then converts monocytes into tumour-associated macrophages (TAMs), resulting in metastasis and drug resistance [97].…”
Section: S100 Proteins In Breast Cancermentioning
confidence: 99%
“…In recent years, reviews on the role of the S100 protein family in various types of cancers, e.g., breast [34] , [35] , pancreatic [27] , colorectal [22] , and lung cancer [36] , have been published. This review aims to address the role of S100 proteins in hematological malignancies, with a special focus on AML.…”
Section: The S100 Protein Familymentioning
confidence: 99%
“…The name was a result of their solubility in 100% saturated ammonium sulphate [4]. There are currently 25 known members of the S100 family, which are tissue-specific [2,5,6]. This protein family has important intracellular and extracellular roles.…”
Section: S100 Protein Familymentioning
confidence: 99%